Development of Power Point Teaching Materials to Improve Students' Understanding of the Learning Material of Aqidah Akhlak Class XII AT MA Darul Falah - MOH. RAFIUDDIN (Penerbit Hellow Pustaka, 2024)
The aim of this research is regarding the development of Power Point teaching materials in the Development of Power Point Teaching Materials in Increasing Students' Understanding of Class XII Moral Creed Learning Materials at MA Darul Falah. This research is a qualitative approach because it occurs in the field, data is collected through interviews, observation and documentation. The results of this research are that power point teaching materials in developing students to understand how power points work in schools must be a strategy in improving power point teaching materials for students' understanding of the moral aqidah learning material found in class XII MA Darul Falah.